2011
DOI: 10.1186/1749-8090-6-49
|View full text |Cite
|
Sign up to set email alerts
|

Management of chest keloids

Abstract: Keloid formation is one of the most challenging clinical problems in wound healing. With increasing frequency of open heart surgery, chest keloid formations are not infrequent in the clinical practice. The numerous treatment methods including surgical excision, intralesional steroid injection, radiation therapy, laser therapy, silicone gel sheeting, and pressure therapy underscore how little is understood about keloids. Keloids have a tendency to recur after surgical excision as a single treatment. Stretching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 7 publications
1
23
1
Order By: Relevance
“…6 Surgery can help to reduce symptoms and signs of keloids in an adult population. 14 It is very prudent for surgeons to apply early surgical interventions to keloids, however, in a pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Surgery can help to reduce symptoms and signs of keloids in an adult population. 14 It is very prudent for surgeons to apply early surgical interventions to keloids, however, in a pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding postoperative adjuvant therapy, we adopt adjuvant pressure therapy using magnets for the treatment of ear keloids, whereas we use postoperative adjuvant steroid injections to the face except ear, chest, upper and lower extremities, abdomen, and pelvic area as previously described. [4][5][6][7] The treatment outcome was recorded as recurrence or nonrecurrence except shoulder area. (Because we do not intend to completely eradicate shoulder keloids; rather, we have tried to reduce the size and symptoms using multiple intralesional steroid injections).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is usually ignored that if the tissue where the tension is observable is in an unbalanced condition, as in the case when a scar is present, the cells cannot properly interpret the message, giving consequent anomalous responses. At this time, one of the reasons explaining the finding of KSs is the constant stretching of injured tissue 36,39. However, the real causes that give rise to a nonphysiological scar are still obscure.…”
Section: Definition Of Scar and Endorsed Hypothesesmentioning
confidence: 99%
“…Our present work, however, revealed that foot keloids can frequently happen around the age of 10 years and consequently, the average age of foot keloids (18 yrs, range from 7 to 43 yrs) are lower than those of other keloids. (Average age of chest keloids is 32 yrs [5], ear keloids 24 yrs [4], and face:34 yrs [6] ) This is true if considering the high incidence of lower extremity trauma in elderly patients. Although one can think that most lower extremity keloids can be covered by socks or footwear, most foot keloid patients have significant functional problems such as limited range of motion of the ankle or toes and difficulty in wearing normal footwear due to hypertrophied wounds.…”
Section: Discussionmentioning
confidence: 99%